2013
DOI: 10.1039/c3cc46736h
|View full text |Cite
|
Sign up to set email alerts
|

New heterocyclic systems to afford microsecond green-light isomerisable azo dyes and their use as fast molecular photochromic switches

Abstract: The use of benzothiazole as an electron-withdrawing group allows obtaining the fastest thermal isomerisation kinetics reported heretofore for neutral azo dyes (70 μs at 298 K). These green light activatable molecules are valuable candidates as molecular photoswitches since they tolerate thousands of working cycles with no sign of fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 25 publications
(23 reference statements)
0
47
0
1
Order By: Relevance
“…Optimization of the azobenzene photoswitch also inspired the investigation of azoheteroarenes. In general, in these compounds, one benzene ring of the azobenzene is substituted by a heterocycle that changes the electronic and steric properties of the molecules . A first promising example was reported by the group of Herges, who showed that azoindazoles presented complete E – Z isomerization, whereas Z – E isomerization, at only 55 %, was still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of the azobenzene photoswitch also inspired the investigation of azoheteroarenes. In general, in these compounds, one benzene ring of the azobenzene is substituted by a heterocycle that changes the electronic and steric properties of the molecules . A first promising example was reported by the group of Herges, who showed that azoindazoles presented complete E – Z isomerization, whereas Z – E isomerization, at only 55 %, was still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…To improve overall performance,many groups have explored the properties of azobenzene variants by altering the substituents on the aromatic rings,f or example,i nb ridged and orthohydroxy azobenzenes. [23][24][25][26][27][28][29][30] Recently,n ovel classes of azoheterocycle photoswitches were reported, [31][32][33][34][35][36] especially arylazopyrazoles,w hich provide quantitative photoswitching and high thermal stability (ca. 1000 days).…”
mentioning
confidence: 99%
“…The lifetime of the primary transient species, supposedly cis isomer, is 300-500 μs ( Table 2). It should be pointed out that the lifetime of this transient species for the compounds under study is close to the lowest limit of the lifetime for the cis isomer (70 μs), which was recently observed for hetarylazo dyes with ben zothiazole and pyrrole cycles [15]. The fast dark recov ery of the initial dyes results in low conversion degrees in the photostationary state, which was observed in the steady state photolysis.…”
Section: Methodsmentioning
confidence: 99%